Quadriceps motor evoked torque is a reliable measure of corticospinal excitability in individuals with anterior cruciate ligament reconstruction - Rodriguez, K. M.; Palmieri-Smith, R. M.; Krishnan, C. (Journal of Electromyography and Kinesiology, 2022)
This study comprehensively evaluated the test-retest reliability of raw and normalized quadriceps motor evoked responses elicited by transcranial magnetic stimulation (TMS) in individuals with anterior cruciate ligament (ACL) reconstruction. Fifteen participants were tested on three different days that were separated at least by 24 h. Motor evoked responses were collected during a small background contraction on the reconstructed leg across a range of TMS intensities using torque (MEPTORQUE) and electromyographic (MEPEMG) responses. MEPTORQUE and MEPEMG were evaluated using different normalization procedures (raw, normalized to maximum voluntary isometric contraction [MVIC], peak MEP, and background contraction). MEPTORQUE was also normalized to the magnetically-evoked peripheral resting twitch torque. The area under the recruitment curve was computed for both raw and normalized MEPs. Intraclass correlation coefficients (ICCs) were determined to assess test-retest reliability. Results indicated that MEPTORQUE generally showed greater reliability than MEPEMG for all normalization procedures. Vastus medialis MEPEMG generally showed greater reliability than rectus femoris MEPEMG. Finally, both MEPTORQUE and MEPEMG exhibited good reliability, even when not normalized. These findings indicate that MEPTORQUE and MEPEMG offer reliable measures of corticospinal function and suggest that MEPTORQUE is a suitable alternative to MEPEMG for measuring quadriceps corticospinal excitability in individuals with ACL reconstruction.